Evaluation of ecosystem health and potential human health hazards in the Hangzhou Bay and Qiantang Estuary region through multiple assessment approaches. (September 2020) - Zhu, Genhai; Noman, Md Abu; Narale, Dhiraj Dhondiram; Feng, Weihua; Pujari, Laxman; Sun, Jun
Abstract: Anthropogenic pollution has become a major issue governing ecosystem and human health risks. The Hangzhou Bay and Qiantang Estuary region are facing unusual perturbation due to rapid development along the embayment in recent decades. This study evaluated the organic and inorganic pollutants in water, sediment, and from the muscles of higher trophic organisms (fish, crustacean, shellfish) during four different seasons (in 2018–2019) along the Qiantang Estuary and Hangzhou Bay region to assess the ecosystem health and potential hazard status. Dissolved inorganic phosphate and nitrogen were the major pollutants in this area, which led to severe eutrophication throughout the study period. Eutrophication signals coincided well with the phytoplankton abundance, which revels the control of nutrient enrichment on the spatio-temporal distribution of phytoplankton. Food availability, along with salinity and temperature, drives the zooplankton population distribution. Heavy metals were not the issue of water quality as their concentrations meet the national and international baseline standards. However, in the sediments, Copper (Cu) and Arsenic (As) concentrations were higher than the baseline value. Towards the northwestern part of the Qiantang Estuary, the overall potential risk index of sediment with higher Cadmium (Cd) and Mercury (Hg) depicted delicate condition with moderate risk for the sediment contamination. The As concentration in fishes was close to the baseline standards limit irrespective of low As values within water and sediments. The higher concentrations of Zinc (Zn) and As in shellfish muscles, whereas other metals were within the limit of baseline standard in all the organisms. However, the hazard analysis (Targeted hazard quotient, THQ) values for the seafood consumption to human health indicates the potentially threatening consequences of shellfish and crustacean consumption on human health. Graphical abstract: Anthropogenic effluents causing eutrophication, heavy meatal pollution and human health risk through aquatic food consumption. Image 1 Highlights: Eutrophication is the major problem in water rather than other pollutants. Eutrophication and other physio-chemical parameters shapes the plankton assemblages. Sediments are in moderate risk condition for heavy metal contamination (Cu, Hg). Metal concentrations are lower in fish than crustacean and shellfish. Crustacean and shellfish consumption are threatening for human health because of As. Abstract : Eutrophication is the major problem in water throughout the year. Cu and As concentrations were higher in sediment and possess moderate risk. High THQ value depicts that crustacean and shellfish consumption would be dangerous for human health due to Zn and As contamination.